PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS V SD NEGERI 060915 JL TB SIMATUPANG KECAMATAN MEDAN SUNGGAL TAHUN PEMBELAJARAN 2018/2019 - HALAWA, WENY GLORY HIDAYATI (Jurnal Ilmiah Aquinas, 2019)
The purpose of this research is to know the effect of make amatch type learning to student learning outcome in mathematics in subject at the fifth grade student of SD 060915. The method of this research was a quasi-experimental research with pretest posttest control group design. The experiment sample was 30 students that used make amatch cooperative learning method. The control sample was 30 students that used speech method. The instruments of this research wasobjective learning outcomes test with 15 questions.The technique of analysis data was t-test. Based on the calculation, t-score showed that t-count was 2,127 and t-table was 1,672 at the significance level of 5% which means t-count > t-table (2,127>1,672), so Ho was rejected and Ha was accepted. It can be concluded that cooperative learning make a match type has positive influence to student learning outcome in mathematics in subject at the fifth grade student of SD 060915 in addition and subtraction of ordinary fragment and mixed fragment concept.